Habits: bridging the gap between personhood and personal identity - Wagner, Nils-Frederic; Northoff, Georg (Frontiers in Human Neuroscience, 2014)
In philosophy, the criteria for personhood (PH) at a specific point in time (synchronic), and the necessary and sufficient conditions of personal identity (PI) over time (diachronic) are traditionally separated. Hence, the transition between both timescales of a person’s life remains largely unclear. Personal habits reflect a decision-making (DM) process that binds together synchronic and diachronic timescales. Despite the fact that the actualization of habits takes place synchronically, they presuppose, for the possibility of their generation, time in a diachronic sense. The acquisition of habits therefore rests upon PI over time; that is, the temporal extension of personal decisions is the necessary condition for the possible development of habits. Conceptually, habits can thus be seen as a bridge between synchronic and diachronic timescales of a person’s life. In order to investigate the empirical mediation of this temporal linkage, we draw upon the neuronal mechanisms underlying DM; in particular on the distinction between internally and externally guided DM. Externally guided DM relies on external criteria at a specific point in time (synchronic); on a neural level, this has been associated with lateral frontal and parietal brain regions. In contrast, internally guided DM is based on the person’s own preferences that involve a more longitudinal and thus diachronic timescale, which has been associated with the brain’s intrinsic activity. Habits can be considered to reflect a balance between internally and externally guided DM, which implicates a particular temporal balance between diachronic and synchronic elements, thus linking two different timescales. Based on such evidence, we suggest a habit-based neurophilosophical approach of PH and PI by focusing on the empirically-based linkage between the synchronic and diachronic elements of habits. By doing so, we propose to link together what philosophically has been described and analyzed separately as PH and PI.